2023
DOI: 10.1007/s10827-023-00849-9
|View full text |Cite
|
Sign up to set email alerts
|

Responses in fast-spiking interneuron firing rates to parameter variations associated with degradation of perineuronal nets

Abstract: The perineuronal nets (PNNs) are sugar coated protein structures that encapsulate certain neurons in the brain, such as parvalbumin positive (PV) inhibitory neurons. As PNNs are theorized to act as a barrier to ion transport, they may effectively increase the membrane charge-separation distance, thereby affecting the membrane capacitance. Tewari et al. (2018) found that degradation of PNNs induced a 25%-50% increase in membrane capacitance $$c_\text {m}$$ c … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
2
3
0
Order By: Relevance
“…The increased capacitance of FSIs at both the 1-hr and 3-day timepoints after PNN removal aligns with previous research 65, 102 . While we did not observe a significant attenuation in AP frequency as previously reported after ABC 31, 65, 103105 , we did find a trend towards a reduction in AP frequency, somewhat consistent with modeling studies demonstrating a reduction in firing frequency when capacitance is increased 102 , the latter which we observed after PNN removal. However, several studies have also reported no effect of ABC on AP frequency 40, 106108 ; the differences with the current finding may be due to species variability 104 , variation in ABC treatment protocols and brain areas, and the duration following ABC treatment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The increased capacitance of FSIs at both the 1-hr and 3-day timepoints after PNN removal aligns with previous research 65, 102 . While we did not observe a significant attenuation in AP frequency as previously reported after ABC 31, 65, 103105 , we did find a trend towards a reduction in AP frequency, somewhat consistent with modeling studies demonstrating a reduction in firing frequency when capacitance is increased 102 , the latter which we observed after PNN removal. However, several studies have also reported no effect of ABC on AP frequency 40, 106108 ; the differences with the current finding may be due to species variability 104 , variation in ABC treatment protocols and brain areas, and the duration following ABC treatment.…”
Section: Discussionsupporting
confidence: 91%
“…The increased capacitance of FSIs at both the 1-hr and 3-day timepoints after PNN removal aligns with previous research 65,102 . While we did not observe a significant attenuation in AP frequency as previously reported after ABC 31,65,[103][104][105] , we did find a trend towards a reduction in AP frequency, somewhat consistent with modeling studies demonstrating a reduction in firing frequency when capacitance is increased 102 , the latter which we observed after PNN removal.…”
Section: Pnn Removal Alters Intrinsic Properties Of Fsis But Does Not...supporting
confidence: 91%
“…PNNs are a form of specialised extracellular matrix that envelops subtypes of neurons, most frequently PV interneurons, providing a protective microenvironment and controlling plasticity (Wingert & Sorg, 2021). PNNs tightly regulate PV interneuron excitability (Hanssen et al, 2023), and removal of PNNs decreases the mean spiking activity and increases the spiking variability of PV interneurons (Lensjø et al, 2017). Previous studies have shown reduced PNN staining surrounding PV expressing interneurons consumption of hypercaloric diets (Dingess et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…One study that did not use chABC, focused on a transgenic or viral knockout of Brevican, a PNN proteoglycan, and found reduced firing rates in PV+ cells (Favuzzi et al, 2017). This paper did not look at effective capacitance, but did find a deficit in KV1.1 and KV3.1 potassium channels, which are important for the fast-spiking phenotype of PV+ cells (Du et al, 1996;Goldberg et al, 2008;Hanssen et al, 2023).…”
Section: Introductionmentioning
confidence: 97%
“…1101/2024 One paper that finds an effect on firing rate with chABC treatment suggests that an increased effective capacitance causes the reduced firing rate they observed in chABC-treated PV+ cells (Tewari et al, 2018). This theory is disputed by modeling the effect of increased capacitance on firing rate where they find that capacitance change alone cannot explain the large reduction (Hanssen et al, 2023). Other factors, like changes in reversal potentials and ion channel conductance, are suggested to be involved.…”
Section: Introductionmentioning
confidence: 99%